1996
DOI: 10.1007/bf02381372
|View full text |Cite
|
Sign up to set email alerts
|

Development of the brain in staged embryos of the long-tailed monkey (Macaca fascicularis)

Abstract: ABSTRACT. The external characteristics and successive morphological changes of the brain and its derivatives were studied in 69 long-tailed monkey embryos representing developmental stages 8 through 16. This morphogenesis follows a similar pattern to those of the rhesus, baboon, and human. Minor differences in the temporal sequence of specific developmental events include: 1) otic disc, adenohypophyseal pouch, and hippocampal internal sulcus formation in the long-tailed macaque occur at stage 10, stage 11, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…The duration of spermatogenesis is 40-46 days compared to 64-74 days in humans (Amann et al, 1976;Amann, 2008;Aslam et al, 1999;Hendrickx and Dukelow, 2005). Organogenesis is also similar in humans and macaques (approximately gestation day 20-50) (Makori et al, 1996). Following organogenesis, macaques undergo an accelerated development relative to humans such that at the time of birth macaques are as developed or more developed than humans (Holsapple et al, 2003;Walthall et al, 2005;Wood et al, 2003;Zoetis et al, 2003;Zoetis and Hurtt, 2003a,b).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…The duration of spermatogenesis is 40-46 days compared to 64-74 days in humans (Amann et al, 1976;Amann, 2008;Aslam et al, 1999;Hendrickx and Dukelow, 2005). Organogenesis is also similar in humans and macaques (approximately gestation day 20-50) (Makori et al, 1996). Following organogenesis, macaques undergo an accelerated development relative to humans such that at the time of birth macaques are as developed or more developed than humans (Holsapple et al, 2003;Walthall et al, 2005;Wood et al, 2003;Zoetis et al, 2003;Zoetis and Hurtt, 2003a,b).…”
Section: Introductionmentioning
confidence: 90%
“…Rhesus macaques (Macaca mulatta) or marmosets (Callithrix jacchus) can also be used although there are certain limitations of using these species, such as seasonal breeding in rhesus macaques (Henck et al, 1996;Wickings and Nieschlag, 1980) and small size and blood volume in marmosets (Fuchs and Weinbauer, 2006;Zuhlke and Weinbauer, 2003). The embryology and fetal development between cynomolgus and rhesus monkeys is very similar Geijsberts, 1981, 1985;Makori et al, 1996Makori et al, , 2003Tarantal and Hendrickx, 1988a,b), and thus the basic research findings in one can be applied to the other in the context of the current report. Baboons and chimpanzees are not acceptable species for DART testing because of their lack of availability, lack of historical control data, and because of the ethical considerations associated with the use of these species.…”
Section: Introductionmentioning
confidence: 96%
“…The teratogenic sensitive period of cRA in the long-tailed monkey occurs during early organogenesis [13] encompassing gestational days (GD) 12-27 [28]. During this period, transient segmentation of the hindbrain into rhombomeres occurs.…”
Section: Introductionmentioning
confidence: 99%
“…Pregnant females (n ϭ 7) were treated once daily via nasogastric intubation with 5 mg/kg/day cRA (dosing volume ϭ 2.5 ml/kg). Initial drug dosing of all the animals was done on GD 12; the duration of treatment and examination of embryos was extended in order to cover the range of developmental stages 10-14 (GD 23-30), which encompasses the early period of brain and pharyngeal arch region development, including cranial NCC formation and migration (Makori et al, 1996;Peterson et al, 1996). Untreated pregnant females (n ϭ 9), used for collection of control embryos, were not administered a vehicle but were handled according to routine procedures for a timed-mated breeding colony, including periodic weighing and ultrasound procedures.…”
Section: Treatment Of Pregnant Animals and Embryo Collection/processingmentioning
confidence: 99%
“…Further development involves invagination to form the otic pits (stage 11, 11-18 somites), which subsequently close off from the surface ectoderm to form the otic vesicle (otocyst) (stage 12, 22-24 somites) (Makori et al, 1996). Detailed studies in chick embryos by Alvarez and Navascues (1990) have shown a four-stage developmental timetable of the otic anlage to form the otic vesicle, which includes shaping, triggering of invagination, early invagination and lateral bending, and late invagination and closure.…”
mentioning
confidence: 99%